2009
DOI: 10.1071/ah090423
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted guideline implementation strategies improve early identification and management of osteoporosis

Abstract: Background: Osteoporosis contributes significantly to fractures, subsequent disability and premature mortality in Australia. Better detection and management of osteoporosis will reduce unnecessary health expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The HARS-14 and CHDS scores of the anxiety–depression group were significantly higher than the control group ( P  < 0.001) whereas the E2 and progesterone levels were significantly lower ( P  < 0.001). The cut-off score for the statistics in Table 2 is 27 (mild cognitive difficulty [21]. An ANCOVA rank sum test (variance arrhythmias) showed that the C-MMSE score in the anxiety–depression group was significantly lower than the control group ( P  < 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HARS-14 and CHDS scores of the anxiety–depression group were significantly higher than the control group ( P  < 0.001) whereas the E2 and progesterone levels were significantly lower ( P  < 0.001). The cut-off score for the statistics in Table 2 is 27 (mild cognitive difficulty [21]. An ANCOVA rank sum test (variance arrhythmias) showed that the C-MMSE score in the anxiety–depression group was significantly lower than the control group ( P  < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…The organic diseases diagnosis was based on the 2007 ESH-ESC (European Society of Hypertension-European Society of Cardiology) Practice Guidelines [19], the 2009 Osteoporosis Guidelines [20, 21] and the standard for early detection of dementia, including mild cognitive impairment [22], blood pressure, poor recognition ability and low bone density. Our study used the Chinese Mini Mental State Examination (C-MMSE) [23, 24] to assess the patient recognition function and the Fan Beam X-ray Bone Densitometer to assess bone density.…”
Section: Methodsmentioning
confidence: 99%
“…Adherence to evidence-based management recommendations is associated with improvement in patient outcomes [ 12 ]. Strategies employed to improve the implementation and use of osteoporosis guidelines have also been shown to result in management plans becoming aligned with best practice [ 13 ]. APCO has identified the following key gaps in osteoporosis screening, diagnosis and in consistent delivery of osteoporosis care in the Asia Pacific region: Clinical guidelines relating to osteoporosis in the Asia Pacific are either unavailable and if they are, are heterogenous in terms of their scope and recommendations made.…”
Section: The Priority Initiative Of Apcomentioning
confidence: 99%